Case Report: A case of Lynch syndrome-related glioblastoma with coexisting MSH2 splicing defect and MSH6 frameshift mutation - Huang, Liwei; Tang, Xiaochun; Cao, Demin; Li, Yulei; Zhu, Xiaoying (Frontiers in Oncology, 2026)
This case report describes a 38-year-old Chinese male with Lynch syndrome (LS)-associated glioblastoma (GBM), harboring concurrent germline NM_000251.3:c.942 + 3A>T and somatic NM_000179.3:c.3261dup mutations. The patient presented with progressive headaches, and imaging revealed a right frontal lobe mass with features suggestive of high-grade glioma. Histopathological and molecular analyses confirmed glioblastoma (WHO grade IV), microsatellite instability-high (MSI-H), and mismatch repair deficiency (dMMR). Familial cancer history, including colorectal and gallbladder malignancies in first-degree relatives, aligned with LS diagnostic criteria. The co-occurrence of MSH2 splicing disruption and MSH6 frameshift mutation synergistically exacerbated genomic instability, highlighting a potential mechanism for LS-driven gliomagenesis. This case underscores the importance of genetic screening in young-onset or familial GBM patients, advocates for integrating molecular profiling into therapeutic decision-making, and expands the understanding of LS-associated CNS tumorigenesis.